1999
DOI: 10.1086/313513
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus Pulmonary Syndrome in Pregnancy

Abstract: This comprehensive case review of hantavirus pulmonary syndrome (HPS) during pregnancy in 5 women characterizes the effect of Sin Nombre virus infection on maternal and fetal outcomes. Histopathologic, serological, and clinical information were evaluated for evidence of vertical transmission. Maternal ages ranged from 20 to 34 years and gestational ages from 13 to 29 weeks. Symptoms, physical findings, and laboratory values other than those related to pregnancy were not noticeably different from those of nonpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
1
27
0
3
Order By: Relevance
“…1 This might explain why we have not found severe consequences on the course of pregnancy. In agreement with the comprehensive study in pregnant women infected by North-American SNV 16 we found no evidence for vertical virus transmission for European hantaviruses.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…1 This might explain why we have not found severe consequences on the course of pregnancy. In agreement with the comprehensive study in pregnant women infected by North-American SNV 16 we found no evidence for vertical virus transmission for European hantaviruses.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, maternal hantavirus diseases has been initially misdiagnosed as HELLP syndrome in patient P.H. Some reports were published in the available literature describing PUUV, 6,10-12 DOBV, 9 Sin Nombre virus (SNV), 15,16 Hantaan virus (HTNV), [17][18][19] and undifferentiated hantavirus infections 20 in pregnancy. In all cases the pregnant women had serious clinical courses, one died from SNV infection 16 (see below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'impact de la grossesse au cours de cette infection est difficile à établir du fait de la faible fréquence de cette association. Cependant, l'état physiologique et immunologique de la grossesse ne semble entraîner que peu de variations dans la présentation clinique et l'évolution de la maladie [8].…”
Section: Discussionunclassified
“…La recherche par RT-PCR de l'ARN viral et les examens sérologiques (recherche d'immunoglobulines M anti-Hantavirus sériques de l'enfant ou sur le sang de cordon) confirment parfois la transmission maternofoetale du virus [1]. Les examens macroscopiques et microscopiques du placenta et l'immunohistochimie testant l'antigène de l'Hantavirus sur les tissus foetaux et placentaires ne confirment qu'exceptionnellement l'infection par le virus [8,10]. Il n'y a aucune donnée dans la littérature concernant l'éventualité d'un diagnostic anténatal dans ce contexte.…”
Section: Discussionunclassified